The Indian in the cupboard - Banks,Lynne Reid et al; Cole,Brock (New York : Viacom New Media, 1995)
Based on the story and motion picture of the same title, introduces the user to the culture and customs of mid-eighteenth century Iroquois life. Helps children improve listening, logic, and problem-solving skills. Features over 450 three-dimensional views, Native American music and voices, eight activities, and thirty-five Iroquois environments.
Keywords: Iroquois Indians; Iroquois Indians; Indians of North America; Toys; Magic